2018
DOI: 10.3390/en11081964
|View full text |Cite
|
Sign up to set email alerts
|

Lightning Impulse Withstand of Natural Ester Liquid

Abstract: Due to the low biodegradability of mineral oil, intense research is conducted to define alternative liquids with comparable dielectric properties. Natural ester liquids are an alternative in focus; they are used increasingly as insulating liquid in distribution and power transformers. The main advantages of natural ester liquids compared to mineral oil are their good biodegradability and mainly high flash and fire points providing better fire safety. The dielectric strength of natural ester liquids is comparab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…It was also observed that streamer patterns for negative polarity are thicker than for positive polarity in natural ester and mineral oil. In [90], inhomogeneity differences in breakdown voltage between natural ester and mineral oils with different electrode arrangements representing different fields in homogeneity factors and different gap distances are reported. Various electrode and conductor arrangements reported in the literature on oil breakdown voltage studies were also documented.…”
Section: Pre-breakdown Phenomenamentioning
confidence: 99%
“…It was also observed that streamer patterns for negative polarity are thicker than for positive polarity in natural ester and mineral oil. In [90], inhomogeneity differences in breakdown voltage between natural ester and mineral oils with different electrode arrangements representing different fields in homogeneity factors and different gap distances are reported. Various electrode and conductor arrangements reported in the literature on oil breakdown voltage studies were also documented.…”
Section: Pre-breakdown Phenomenamentioning
confidence: 99%
“…inadequate legislation (standards-defined operational limits) that make the wider industrial use of natural esters more demanding, along with durability problems in terms of lower lightning impulse (LI) resistance [8], [9], oxidative stability, etc. Esters and natural esters also have many benefits, e.g., a low degree of cellulose polymerization (in the system) compared to mineral fluids [10], a high flash point and fire point [11] and a relatively high ''moisture tolerance'' of its dielectric properties [12], higher permittivity is prone a better electric field distribution in the paper-oil system [42] and esters have better thermal stress performance [43].…”
Section: Introductionmentioning
confidence: 99%
“…Experimental investigations dedicated towards the performance of natural esters have been presented in [6,7]. Haegele et al [6] reported the degree of inhomogeneity differences in breakdown voltage between natural ester and mineral oils while using lightning impulses at different electrode arrangements representing different fields in homogeneity factors and different gap distances. Authors also envisaged different electrode and conductor arrangements reported in the literature for oil breakdown voltage studies.…”
Section: A Review Of the Special Issuementioning
confidence: 99%